Indonesia's Capital Market Reaction to the Announcement of BI Rate Reduction in 2025: An Event Study on Property and Real Estate Sector Companies on the Indonesia Stock Exchange - Panji Garjito Adhinegoro; Sofie Sofie (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The announcement of changes in Bank Indonesia's benchmark interest rate is public information that has the potential to affect investor reactions because it changes expectations of economic conditions and the company's prospects in the capital market. This study aims to analyze the market's reaction to the five announcements of a BI Rate reduction in 2025 for property and real estate sector companies listed on the Indonesia Stock Exchange through changes in stock prices, trading activities, and volatility in securities returns. The study uses a quantitative approach with the event study method on five BI Rate announcement dates with an event window of 15 days on the stock exchange (t−7 to t+7). The research sample consisted of 92 companies selected using purposive sampling. The analysis was carried out using a market-adjusted model to calculate the expected return, while the market reaction test was carried out with a one-sample t-test, a paired-sample t-test, and a Wilcoxon signed-rank test according to the characteristics of the data. The results of the study show that the market reaction is different at each announcement of a BI Rate cut. The January and August announcements triggered a stronger stock price reaction, May showed the most prominent changes in trading activity and return variability, July reflected the accumulation of negative returns, while the positive response in September did not fully hold up during the observation period. These findings show that the content of information on the BI Rate reduction is dynamic and is influenced by the timing of the announcement and the observed dimensions of market reactions.